Pengaruh Latihan Ball Feeling Dan Latihan Zig-Zag Terhadap Peningkatan Kemampuan Dribbling Bola - Najamuddin, Muhammad Reza; irfan, Irfan; Musfira A, Nurul; Hudain, Muh. Adnan; Rusli, Rusli (UNIVERSITAS NEGERI MAKASSSAR, 2025)
The type of research in this thesis is an experimental research. This study aims to determine: 1) The effect of ball feeling training on improving ball dribbling skills in futsal extracurricular students of SMP IT Alfityan Gowa. 2) The effect of zig-zag training on improving ball dribbling skills in futsal extracurricular students of SMP IT Alfityan Gowa. 3) The difference in the effect of ball feeling training and zig-zag training on improving ball dribbling skills in futsal extracurricular students of SMP IT Alfityan Gowa. The population in this study were students of SMP IT Alfityan Gowa with a sample of 20 students using random sampling techniques and a group division system using MSOP (Matched Subject Ordinal Pairing). The research instruments used were descriptive analysis, data normality, homogeneity analysis and t-test analysis with the help of the SPSS application version 21.00. The results of the study showed that: (1) There is an influence of ball feeling training on increasing the ability to dribble the ball in extracurricular futsal students at SMP IT Alfityan Gowa, as evidenced by an increase in speed from an average value of 20.6220 to 16.6560 with an observation value of 15.926 > ttable 2.262 and a significant value of 0.000 < α0.05.; (2). There is an influence of zig-zag training on increasing the ability to dribble the ball in extracurricular futsal students at SMP IT Alfityan Gowa, as evidenced by an increase in speed from an average value of 20.5720 to 15.0020 with an observation value of 14.595 > ttable 2.262 and a significant value of 0.000 < α0.05.; (3) There is a difference in the influence of ball feeling training and zig-zag training on improving the ball dribbling ability of extracurricular futsal students at SMP IT Alfityan Gowa with a difference value of 16.6560 < 15.0020 with an observation value of 4.295 > ttable 2.101 and a significant value of 0.000 < α0.05. The conclusion is that zig-zag training has a greater influence compared to ball feeling training on improving the ball dribbling ability of extracurricular futsal students at SMP IT Alfityan Gowa.